Enhancing customer retention: the role of customer satisfaction and delight in the authorized automotive after-sales service sector - Leong, Choi-Meng; Cheah, Jun-Hwa; Ting, Hiram; Lim, Rodney; Ariffin, Adlin Baizura; Lim, Xin-Jean (Sarawak Research Society, 2024)
This study examines the influence of utilitarian and hedonic experiences, customer engagement, and customer value anticipation on customer retention in the authorized automotive after-sales service sector, using customer satisfaction and customer delight as mediators. We collected 316 samples and employed Partial Least Squares-Structural Equation Modeling for data analysis. The findings confirm the direct impacts of utilitarian and hedonic experiences, customer engagement, and customer value anticipation on both customer satisfaction and customer delight. Additionally, customer satisfaction and customer delight directly influence customer retention and mediate the relationship between the hypothesized predictors and customer retention. This research enriches the customer retention literature by integrating Expectancy Disconfirmation Theory with flow theory, customer engagement theory, and customer value theory. It also provides insights into the predictors of customer retention and the mediating roles of customer satisfaction and customer delight in the authorized automotive after-sales service sector. The results suggest that service providers innovate their offerings and focus on enhancing customer satisfaction and delight to meet and exceed customer expectations.